2004
DOI: 10.1093/tropej/50.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Giardia Infection on Growth and Psychomotor Development of Children Aged 0–5 Years

Abstract: Giardiasis, an intestinal protozoan infection caused by Giardia intestinalis, is common in southeastern Anatolia, Turkey. In this cross-sectional survey, to investigate the role of giardiasis on growth and psychomotor development, we studied 160 children aged 0-5 years. Data were collected using a structured questionnaire, anthropometry, Ankara Developmental Screening Inventory, and laboratory analysis of fecal samples. The results showed that 50 per cent of the subjects were infected with at least one pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 0 publications
5
67
0
4
Order By: Relevance
“…have been reported to have adverse affects on linear growth 44,45 and possible consequences for psychomotor development. 46 We therefore suggest that the greater chronicity of protozoan infection in children from dense homes is an important cause of the more severe stunting observed in these children.…”
Section: Discussionmentioning
confidence: 86%
“…have been reported to have adverse affects on linear growth 44,45 and possible consequences for psychomotor development. 46 We therefore suggest that the greater chronicity of protozoan infection in children from dense homes is an important cause of the more severe stunting observed in these children.…”
Section: Discussionmentioning
confidence: 86%
“…In combination with diarrhoea, giardiasis leads to iron deiciency anaemia, micronutrient deiciencies, protein-energy malnutrition, growth and cognitive retardation and malabsorption [31]. Studies from Peru and Brazil found that diarrhoea disease occurring in the irst 2 years of life negatively correlates with verbal luency, cognitive function and may lead to long-term growth failure [32].…”
Section: Nutritional Consequencesmentioning
confidence: 99%
“…duedonalis) kamçılı bir protozoon parazit olup her yıl 280 milyon insan vakası oluşturduğu düşünülmektedir (11). Dispepsi, diyare, steatore ve meteorizme sebep olmakta ve çocuklarda malnutrisyon yaratmaktadır (12,13).…”
Section: Introductionunclassified